Fatwas and Humanitarian Actions: The Political Role of Acehnese Ulama in the Rohingya Refugee Crisis - Nurul Akmaliyah; Nengsih (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2025)
This article examines the political role of ulama in responding to the refugee crisis in Aceh. In the broader literature on religion and refugee governance, religious actors are often portrayed as having a limited role. This study challenges that assumption by analyzing the case of Aceh, where ulama actively fostered solidarity with Rohingya refugees. The article demonstrates that Acehnese ulama not only articulated moral narratives grounded in Islamic values but also mobilized their political authority to pressure the government to adopt more humane and accountable policies. Employing a qualitative case study design, this research explores both the moral and politicaldimensions of religious leadership in the crisis. Data were collected through the analysis of official documents—such as Fatwa No. 3 of 2024 and Tausyiah No. 6 of 2024—as well as print and digital media that capture public narratives articulated by ulama. The article argues that, in the Achenese context, religion functions not merely as a moral compass but also as an effective political instrument for policy intervention and the construction of transnational solidarity rooted in local values. These findings highlight the importance of incorporating religious actors into governance frameworks for refugee crises, particularly in societies where religious institutions play a central role.